2018
DOI: 10.26483/ijarcs.v9i1.5348
|View full text |Cite
|
Sign up to set email alerts
|

SMART CROP FIELD IRRIGATION IN IoT ARCHITECTURE USING SENSORS

Abstract: This Paper deals with the improvement of growth of crops by means of managing and monitoring the soil texture. The automated irrigation system has been designed and implemented helps the farmers efficiently by all means. The system developed is very useful and works in cost effective manner. It manages the water consumption to a greater extent mainly during the rainy season. It needs minimal maintenance and the power consumption is also greatly reduced. This system can be used in large field. The crop producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…[100] also created an automated irrigation system using Arduino technology. Savitha and Maheshwari [101] also devised the concept of an automated and effective watering system by creating remote sensors with Arduino technology, which can boost the output by as much as 40%. Zimdahl [102] conducted extensive research on the subject and concluded that weeds were the greatest rivals for water, with plants starting to compete for water and nutrients when their roots overlapped in the soil.…”
Section: Automation and Robotics In Agriculturementioning
confidence: 99%
“…[100] also created an automated irrigation system using Arduino technology. Savitha and Maheshwari [101] also devised the concept of an automated and effective watering system by creating remote sensors with Arduino technology, which can boost the output by as much as 40%. Zimdahl [102] conducted extensive research on the subject and concluded that weeds were the greatest rivals for water, with plants starting to compete for water and nutrients when their roots overlapped in the soil.…”
Section: Automation and Robotics In Agriculturementioning
confidence: 99%
“…Jha et al [62] have also developed an automated irrigation system with Arduino technology to decrease human power and time consumption in the irrigation process. The concept of an effective and automated irrigation system was also created by Savitha and Uma Maheshwari [63] by developing remote sensors using Arduino's technology that can increase output by up to 40 percent. One of the many technologies used to measure the quality of soil moisture is used by soil moisture sensors.…”
Section: Irrigationmentioning
confidence: 99%
“…"Monitoring contains modules like remainder, plant growth monitoring in various stages, irrigation planner, crop profit calculator, calamity check and problem identifier" (Mohanraj et al, 2016). According to the agricultural areas the prediction data varies and it is provided to the farmers so that they can plan for their farming (Savitha, UmaMaheshwari, 2018).…”
Section: Introductionmentioning
confidence: 99%